Calculation in the pirate bazaars. Issue 5 (3rd September 2017) - Deka, Maitrayee
ABSTRACT: Recent debates in economic sociology have focused on the question of long-term calculation specific to capitalism. With a renewed interest in Max Weber's work, particularly his seminal essay, The protestant ethic and the spirit of capitalism, scholars such as Arjun Appadurai and Jens Beckert have analysed calculative devices intrinsic to long-term accounting. Appadurai highlights the charismatic figure of the financial player who speculates on uncertainty, the same realm of uncertainty that in Beckert's work becomes intelligible through the creation of market fictions. In this paper, I instead explore calculation as it unfolds in bazaars selling contraband and pirated electronic goods. Based on an ethnographic account of Delhi's Lajpat Rai market, Palika Bazaar, and Nehru Place, I argue that calculation in the pirate bazaars is of a short-term nature and oriented to an embedded economic rationality that is closely entangled with the longue durée of everyday life. Rather than future-oriented fictions, small-scale traders employ moral stories and piracy-related discourses to meet day-to-day survival needs.